2011
DOI: 10.1098/rspb.2011.1647
|View full text |Cite
|
Sign up to set email alerts
|

Relationship satisfaction and outcome in women who meet their partner while using oral contraception

Abstract: Hormonal variation over the menstrual cycle alters women's preferences for phenotypic indicators of men's genetic or parental quality. Hormonal contraceptives suppress these shifts, inducing different mate preference patterns among users and non-users. This raises the possibility that women using oral contraception (OC) choose different partners than they would do otherwise but, to date, we know neither whether these laboratory-measured effects are sufficient to exert real-world consequences, nor what these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 31 publications
2
46
1
1
Order By: Relevance
“…Sexual satisfaction scores were included as a covariate in the model predicting nonsexual satisfaction, and vice versa (cf. Roberts et al, 2012). We again found a significant main effect of congruency for women's sexual satisfaction scores, F(1, 335) = 4.02, p = .046, η p 2 = .012; higher scores were reported by women whose previous and current contraceptive use was congruent rather than noncongruent (for full results of the models, see Table S1 in the Supplemental Material available online).…”
Section: Contraceptive Congruencymentioning
confidence: 53%
See 2 more Smart Citations
“…Sexual satisfaction scores were included as a covariate in the model predicting nonsexual satisfaction, and vice versa (cf. Roberts et al, 2012). We again found a significant main effect of congruency for women's sexual satisfaction scores, F(1, 335) = 4.02, p = .046, η p 2 = .012; higher scores were reported by women whose previous and current contraceptive use was congruent rather than noncongruent (for full results of the models, see Table S1 in the Supplemental Material available online).…”
Section: Contraceptive Congruencymentioning
confidence: 53%
“…OC use could therefore potentially influence both a woman's initial partner choice (if she uses OCs during relationship formation) and changes in her subsequent satisfaction with that choice (if she subsequently discontinues or initiates OC use; Roberts et al, 2012). Furthermore, because women's attractiveness to men also varies with menstrual cycle phase and OC use (Cobey, Buunk, Pollet, Klipping, & Roberts, 2013;Haselton & Gildersleeve, 2011;Havlíček, Dvorakova, Bartos, & Flegr, 2006;Kuukasjärvi et al, 2004;Puts et al, 2013), men's relationship satisfaction might also be influenced by changes in their partners' OC use.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, HC use alters women's pair-bonding behavior, evident in decreased attractiveness ratings of masculine faces (Little et al, 2013), reduced neural response to the expectation of erotic stimuli (Abler et al, 2013), a preference shift towards olfactory cues of genetic similarity (Roberts et al, 2008) and increased sexual jealousy (Geary et al, 2001). Furthermore, women who use HC while choosing partners are more likely to initiate an eventual separation (Roberts et al, 2012) and wives who discontinue HC use tend to be less satisfied with marriage if they perceive their husband's face to be less attractive (Russell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Roberts et al (21) reported that women who used HCs when Significance Hormonal contraceptives (HCs) are believed to suppress biological processes associated with women's preferences for cues of partner genetic fitness, cues that may be summarized by men's facial attractiveness. Two longitudinal studies of marriage demonstrate that wives who used HCs at relationship formation became less satisfied when they discontinued HCs if their husband had a relatively less attractive face, but more satisfied if their husband had a relatively more attractive face.…”
mentioning
confidence: 99%